A trend analysis based on tourist market profile Data of Sri Lanka - Amaresh, M.; Anandasayanan, S. (Sabaragamuwa University of Sri Lanka, 2020)
Tourism has been playing a key role in global economy while creating employment opportunities, generating export revenue and adding value to the domestic resources. It has become a fastest growing sector and important economic sector across the globe, specifically in developing countries such as Sri Lanka. The international tourist arrival was 1.4 billion and international tourism export was US$ 1.7 trillion (SLTDA annual report, 2018). As per SLTDA monthly report 2019, the total number of international tourists to Sri Lanka was 1913702 in 2019. This study aimed to analyze the overall trends in tourist arrivals and to identify the recent trends in profile characteristics of tourist arrivals in Sri Lanka. Overall trends delineated in this article are based on the statistical data from 2000 to 2019.The prominent features of tourists such as age, gender, occupation, period of stay and purpose of visit were analyzed by employing three year moving average method and regression analysis with the help of MS Excel. Analyzing the trends is important for creating demand for hotel accommodation, economic development, job creation and infrastructure development by the government. Pleasure/holiday and visiting friends are the only two purposes of visit of tourists that showed increasing trend. In age group, 60 years and over, 50-59 years and 20-29 years showed an increasing trend and 50-59 age group indicated a remarkable increasing trend during the study period. Further, the investigation confirmed that female tourist arrival showed a significant increasing trend whereas male tourist arrival showed decreasing trend. The trend of period of stay depicted that international visitors preferred to stay lengthy nights in Sri Lanka as the periods of stay 22- 30 nights, 15-21 nights, 31 nights and more. Further, 4-7 nights and 8-14 nights showed increasing trend and remarkably 15-21 nights stay of tourists increased. The present study also concluded that only retired person category is showing a low and increasing trend.
Keywords: Foreign Exchange; Market Profiles; Sri Lanka; Tourist Arrivals